Perancangan Sistem Informasi Absensi Dan Nilai Siswa Beserta Absensi Dan Laporan Kegiatan Guru Di Sekolah Advent Pancaran Kasih Berbasis Web - Boston Pahala Siahaan; Yusran Timur Samuel (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
Generally attendance system and teacher activity report in school is done by manual that is teacher fillthe attendance by writing in paper of their attendance data after that teacher also doing attendancefor student by calling student name one by one done by teacher teaching. Therefore, it needs a changewith the computerization process to fix any deficiencies and fraud in the process of absenteeism andvalue on the students. Sekolah Pancaran Kasih is very eager to have a useful school website to provideinformation - information, teacher and student attendance along with better student scores. Systemdevelopment method used in this research is SDLC consisting of (1) Information, (2) design, (3)implementation, (4) maintenance. From this research which have been done, the writer conclude that(1) This system can be used by teacher and admin (2) teacher easily input student attendance dataand give value to its student (3) All attendance data and student value and teacher attendance dataand the activity report will be saved to the system that has been created. With the design of attendanceinformation system and students' values along with absences and reports of teacher activities it can beconcluded, the system can provide convenience to users and administrators involved in processing andstoring data so as to provide information in accordance with the needs of the user.